2001
DOI: 10.1177/0032885501081001004
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Costs of Imprisonment for Women: Complications of Reintegration

Abstract: This article examines issues of family separation and community isolation as experienced by women on parole. Qualitative data, based on unstructured, in-depth interviews with 54 former inmates, offer retrospective reflections and current accounts that delineate many of the unintended costs of imprisonment. The narratives portray the difficulties these women experienced in parenting, relationships, and community reintegration. Social stigma and self-shame are important definitional and reactional elements of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
151
1
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(166 citation statements)
references
References 16 publications
1
151
1
13
Order By: Relevance
“…Other researchers have come to similar conclusions regarding the potential risk factors that women on parole face (e.g., Cobbina, 2009Cobbina, , 2010Dodge & Pogrebin, 2001;Huebner, Dejong, & Cobbina, 2010;O'Brien, 2001;Richie, 2001). Richie (2001) suggested that newly released women need access to substance abuse treatment in the community to continue their treatments and to find support systems outside of prison.…”
Section: Prisons Should Focus On Reentrymentioning
confidence: 83%
“…Other researchers have come to similar conclusions regarding the potential risk factors that women on parole face (e.g., Cobbina, 2009Cobbina, , 2010Dodge & Pogrebin, 2001;Huebner, Dejong, & Cobbina, 2010;O'Brien, 2001;Richie, 2001). Richie (2001) suggested that newly released women need access to substance abuse treatment in the community to continue their treatments and to find support systems outside of prison.…”
Section: Prisons Should Focus On Reentrymentioning
confidence: 83%
“…Most women, particularly women of color, return to impoverished neighborhoods following release from prison (Dodge & Progrebin, 2001;Owen & Bloom, 1995;Richie, 2001). In fact, Richie (2001) found that African-American women are more likely to report a lack of access to programs and services in their disenfranchised communities.…”
Section: Reentry Contextmentioning
confidence: 99%
“…When mothers are sent to prison, substitute childcare is of upmost importance (Morris, 1991). If relatives or friends are unable to take guardianship, the child will enter the care system, preventing barriers for mothers to regain potential rights on release (Dodge and Pogrebin, 2001). The loss of the mother role is considered as significant pain of imprisonment for women and can leave women with loss of identity and low self-esteem (Corston report as cited by Amanda, 2008).…”
Section: Introductionmentioning
confidence: 99%